2014
DOI: 10.1111/iwj.12262
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of foot ulceration in people with chronic gout

Abstract: Gout is the most common form of inflammatory arthritis and it has an affliction to the foot. Foot involvement in gout has been linked to foot pain, impairment and disability. There has been limited research on the effect of ulceration on foot pain, impairment, disability and health-related quality of life in patients already living with gout. The aim of the study was to describe the wound characteristics and the effect on foot pain, disability and health-related quality of life in patients with foot ulceration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…This finding is not dissimilar to baseline scores reported in other research . Our sample reported higher scores for all sub‐scales of the CWIS than people who have gout‐related foot wounds and slightly higher physical symptom and daily living scores than people with lower leg ulcers . Our sample reported similar baseline CWIS sub‐scales and overall scores for participants of a compression therapy RCT , a cell‐grafting evaluation and a pilonidal sinus disease study .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This finding is not dissimilar to baseline scores reported in other research . Our sample reported higher scores for all sub‐scales of the CWIS than people who have gout‐related foot wounds and slightly higher physical symptom and daily living scores than people with lower leg ulcers . Our sample reported similar baseline CWIS sub‐scales and overall scores for participants of a compression therapy RCT , a cell‐grafting evaluation and a pilonidal sinus disease study .…”
Section: Discussionsupporting
confidence: 74%
“…Several studies using the CWIS have investigated quality of life at one time point or over time. Moderate to good quality of life among older men with gout‐related foot wounds has been reported for the social life score (mean 61·0, SD 24·3), well‐being score (mean 73·3, SD 15·4) and physical symptoms and daily living score (mean 66·7, SD 28·5) . A study investigating the quality of life of leg, foot and pressure injury patients receiving negative pressure wound therapy found that people receiving the intervention had improved social life scores during the first 2 weeks when compared to controls; however, there were no other significant differences for other sub‐scales of the CWIS at a range of time points up to 12 weeks .…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, most patients presented ulceration in 1 area, whereas several patients suffered from multiple ulcerations. The present study also found that ulceration over tophi was most commonly seen in feet (MTP and ankle), which was in line with previous studies, which may be attributed to the biomechanical loading or physical stress during the normal gait cycle …”
Section: Discussionsupporting
confidence: 93%
“…Although those comorbidities were not included in the regression model, they all have a potential effect on the formation of ulceration. Rome et al reported a study of the clinical characteristics of foot ulceration in people with chronic gout , which showed that those affected were predominantly older men with a long duration of gout and that most wore shoes that were considered poor footwear. The present study also found that lack of protective sensation was independently associated with ulceration over tophi, suggesting that careful monitoring of people with gouty ulceration is warranted.…”
Section: Discussionmentioning
confidence: 99%